Design of a network of cycling routes in the Kutná Hora district - Lukáš Vacka; Pavel Vrtal; Tomáš Kohout (Acta Polytechnica CTU Proceedings)
Cycling is a dynamically expanding transport mode of today. At the same time, cycling is an alternative to individual car transport as well as to public transport. The basis of a good cycling infrastructure is a comprehensive network of safe cycling routes linking transport sources and destinations in the area. The partial objectives of the project are to evaluate the management of the existing cycle routes according to the way cyclists are guided and according to the surface of the individual route sections, as well as to determine the basic sources and destinations. The main objectives of the project are to design a network of bicycle routes with a focus on keeping them separate from motorized traffic and linking the identified resources and destinations, as well as determining the difficulty of each newly proposed route.